Exploring whiteness in the context of anti-racist practice: A mixed methods survey - Basset, Frances (European Journal for Qualitative Research in Psychotherapy, 2022)
A growing body of evidence exposes the persistence of racism and inequality within the psychological professions and this has led to a re-commitment across allprofessional bodies to address this as a matter of high importance. This study aims to illuminate therapists’ views and understandings of the social construct and term“whiteness” within anti-racist practice. A short, mixed-methods survey conducted in the United Kingdom sought therapists’ views and from a purposive sample of 150andfifty were returned. Quantitative data were statistically analyzed and Reflexive Thematic Analysis (RTA) was utilized to explore qualitative data. Results suggest that respondents believe that the terms “whiteness”and “white culture”reflect a dominant, yet often invisible,force in the field of race, and culture. Dialogue inclusive of the meaning and power of whiteness needs to be addressed in anti-racism training and education. A central organizing concept “Heart of the Work”was the connecting principle between four key themes: The Dominance of Whiteness; Ambivalence, Complexity and Uncertainty; The Importance of Education; and Understanding the Wider Context. Findingsfrom this survey indicates that discussions about whiteness, privilege, and racial identity could enhance anti-racism within psychotherapy. There is a real concern about the re-traumatization of racially-minoritized members of therapy training groups, and the requirement for reflexivity and skilled facilitation is highlighted.